2011
DOI: 10.1080/13607863.2011.569488
|View full text |Cite
|
Sign up to set email alerts
|

The ratio between positive and negative affect and flourishing mental health across adulthood

Abstract: Using data from a 30-day diary study with 239 adults (81 young, 81 middle-aged, and 77 older adults) this study examined whether a specific ratio between positive and negative affect distinguished individuals with different mental health status and especially flourishing from nonflourishing individuals. In addition, the study addressed whether there were age differences in the positivity ratio when daily affect data were used, and whether the proposed critical positivity ratio of 2.9 discriminated equally well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 47 publications
6
97
1
5
Order By: Relevance
“…This provide them to have more accurate self-perceptions and selfappraisals (i.e., without self-enhancement or selfdeprecation) than those lacking (Leary et al, 2007). Similarly since flourishing is related to (and also facilitate) feelings of wellness, resilience (Fredrickson & Losada, 2005;Larsen & Prizmic, 2008), and a balance between positive and negative affect (Diehl et al, 2011), that people experience when they are self-compassionate flourishing and self-compassion may seem alike in nature and the positive associations between self-kindness, mindfulness, and flourishing are not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This provide them to have more accurate self-perceptions and selfappraisals (i.e., without self-enhancement or selfdeprecation) than those lacking (Leary et al, 2007). Similarly since flourishing is related to (and also facilitate) feelings of wellness, resilience (Fredrickson & Losada, 2005;Larsen & Prizmic, 2008), and a balance between positive and negative affect (Diehl et al, 2011), that people experience when they are self-compassionate flourishing and self-compassion may seem alike in nature and the positive associations between self-kindness, mindfulness, and flourishing are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies it was found that flourishing associated positively with emotional vitality (Michalec et al, 2009), positive emotions, life satisfaction, resiliency, autonomy, productivity, competency, personal adjustment and development (Diehl et al, 2011;Diener et al, 2010;Keyes, 2002;Telef, 2011), self-acceptance (Diener et al, 2010), mindfulness, and positive emotional reactivity (Catalino & Fredrickson, 2011) and negatively to depression (Keyes, 2002), mental illness (Michalec et al, 2009), and negative affect (Diehl et al, 2011;Keyes, 2002). Also studies suggest that individuals with a sense of flourishing are more likely to contribute to their communities (Huppert, 2009;Michalec et al, 2009), are more productive at work, enjoy better social relationships, experience less limitations on daily activities (Huppert, 2009;Keyes, 2005), have higher levels of environmental control, positive relations with others (Telef, 2011), and relatedness, lower levels of loneliness (Diener et al, 2010;Gokcen, Hefferon, & Attree, 2012).…”
Section: Flourishingmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency that a person experiences positive versus negative emotions is termed the positivity ratio, and is a widely-used indicator of well-being in positivity research [8,9]. Among adults, this ratio has distinguished individuals who lead a flourishing life -full of meaning, possibility, and growth -from those who desire more meaning and purpose [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is reason to believe that adolescents who experience a greater ratio of positive to negative emotions benefit from a broadened range of perceptions, ideas, and actions [2] -the broaden effect -and that over time, repeated experiences of positivity build a variety of enduring personal and environmental resources such as improved adaptation to adversity and greater resilience, [3] more thoughtful decision making, and greater social connection [4] -the build effect [5,6]. Conversely, adolescents experiencing too few and/or dysregulated positive emotions would report poorer emotional functioning, including increased stress and depressive symptoms [7].The frequency that a person experiences positive versus negative emotions is termed the positivity ratio, and is a widely-used indicator of well-being in positivity research [8,9]. Among adults, this ratio has distinguished individuals who lead a flourishing life -full of meaning, possibility, and growth -from those who desire more meaning and purpose [7].…”
mentioning
confidence: 99%